Dental laser at transition times toward the post-pandemic - Jorge Homero Wilches Visbal; Isabella Cahuana Mercado; Angely Andrea Olaya Ribaldo (Revista Cubana de Medicina Militar)
Despite the fact that dental lasers are more expensive than traditional instruments, it is cheaper and more commendable to avoid the appearance of resurgence of the disease that promote mistrust in patients, to the detriment of themselves and the economic recovery of the dental sector, while herd immunity is achieved.